Three dimensional phenomena driven scientific inquiry using interactive learning spaces effects on students' digital creativity and adversity quotient - Pobadora, Jasmin C.; Paderna, Edwehna Elinore S.; Ramirez, Hazel Joyce M.; Que, Elenita N.; Cauyan, Jaclyn Marie L. (Quezon City College of Education, University of the Philippines Diliman, 2025)
Approaches to teaching play a crucial role in enhancing students' digital creativity and adversity quotient. Science teachers are encouraged to adopt methods that equip students with skills for a more digitized and challenging future, promote science literacy, and foster resilience even during educational emergencies. These objectives inspired the development of the science instruction termed Three-Dimensional Phenomena-Driven Scientific Inquiry Using Interactive Learning Spaces (3PSI). This study specifically examined the effects of 3PSI on students' digital creativity and Adversity Quotient and explored whether digital creativity is a positive predictor of adversity quotient and vice versa.

The research employed a quasi-experimental design involving two randomly selected Grade 10 classes from a public high school in Antipolo City, Rizal. These sections were randomly assigned to either 3PSI or conventional instruction (CI). The instruments utilized were the Digital Creativity Tasks (DCT) and the Adversity Quotient Profile (AQ Profile). The DCT, a researcher-developed instrument, underwent expert validation and pilot testing, with inter-rater reliability established using the intraclass correlation coefficient (ICC). The AQ Profile, an online instrument designed by Dr. Paul Stoltz in 1997, is recognized as the most robust tool for measuring Adversity Quotient (PEAK Learning Inc., 2024)

To analyze the effects of the intervention, the mean post-task scores for DCT were subjected to analysis of covariance (ANCOVA), while the mean post-test scores for AQ Profile were analyzed using an independent samples t-test. The findings indicated that students exposed to 3PSI achieved significantly higher levels of digital creativity compared to those in conventional instruction, However, 3PSI did not have a significant effect on students’ adversity quotient.
Thesis
Includes bibliographical references (143-149 leaves)
Keywords: Science -- Study and teaching (Secondary) -- Philippines -- Antipolo City; Science -- Study and teaching (Secondary) -- Philippines -- Antipolo City -- Aids and devices; Educational technology -- Philippines -- Antipolo City; Computer-assisted instruction -- Philippines -- Antipolo City; Creative ability -- Philippines -- Antipolo City